The Political and Civic Involvement of Students: a sociological research - Vasiliu, Roxana-Mihaela (Technium Social Sciences Journal, 2020)
On a democratic society, it is desirable to consolidate the relation between citizens and political system through a participatory political culture. Romania – as others post-communism spaces – is characterized by a low level of political communication, poor civic involvement and insufficiently cooperation between government and citizens. During this context, the position of the new generation is crucial in consolidating democracy. Previous studies showed that the young Romanian is perceived rather as an outsider in the relation with the system, have a low trust in institutions by comparison with other age categories, and is not optimistic regarding the capacity of public contestation. On long term, these issues can lead either to a decrease of interest on civic engagement and – in time – to the emergence of a democratic deficit or a subject political culture, or to the emergence of anti-system positions. Nowadays, young people have new tools to help developing a participatory culture, such as new media, new forms of political socialization, an increasing interest in non-governmental organizations et. al. The purpose of the paper is to approach a set of indicators specific to civic and political involvement, using data from a sociological quantitative study conducted on a sample of 430 undergraduates’ students from three specializations: Sociology, Social Work and Human Resources (“Alexandru Ioan Cuza” University of Iasi), in order to observe their civic and political attitudes.